Case Report : Generalized Myasthenia Gravis - Widjaja, Devita; Puspitasari, Vivien (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Generalized myasthenia gravis is a rare case of autoimmune wherein the antibodies destroy the post-sinaptic acetylcholine receptors at skeletal muscle’s neuromuscular junctions. The clinical presentation is specific distributin of motoric deficit without sensoric deficit which diminished with rest and worsens with excessive use. We report a case of a woman 52 yo with symptoms of ptosis, diplopia and dificulty of swallowing. Repetitive nerve stimulation showed >10% decrement and prostigmin test was positive. The patient was treated and showed clinical improvement.